Dynamics Of Tasawuf Morals: The Effect Of Urban Migration On The Decline Of The Quality Of Faith And Religious Practice - Nurhasanah, Natasha Aulia (Ulumuddin: Journal of islamics Study, 2025)
This study examines the impact of urban migration on the quality of faith and religiosity, focusing on the dynamics of Sufism morality among individuals who experience a change in environment from rural to urban. This topic was chosen because increasing urbanization often has an impact on changes in spiritual values ​​and religious practices, especially among the younger generation. Fast-paced, materialistic, and individualistic urban life often poses a major challenge to the preservation of moral values ​​and spirituality. This study uses a quantitative approach with observations of 2 individuals who migrated to big cities in the last five years. The research instrument includes observations designed to measure the level of faith, involvement in religious practices, and understanding of Sufism values. The results of the study show a decline in the quality of faith and intensity of religious practices in most respondents after migration. The main influencing factors are work pressure, the temptation of a modern lifestyle, and the lack of religious communities in urban environments. This study highlights the importance of community support and technology-based adaptation strategies to maintain the quality of faith amidst the challenges of urbanization.